A Failed Attempt to Create an International Community of Communist Asian Studies in 1955. Issue 2 (1st June 2022) - Chen, Huaiyu
Abstract: East German sinologists organized an international conference on East Asian studies in Leipzig in October 1955, bringing together scholars from most communist states and several scholars from Western Europe. This conference served to unite sinologists from both the Communist Bloc and West Germany in the early Cold War era. Since the Chinese delegation was particularly honored, this article suggests that China expanded its political influence in East Europe after the Korean War and the death of Stalin, which prompted a tension within the international communist community, especially between China and the Soviet Union. Moreover, this conference demonstrated a strong "modern turn" in the rising field of Asian studies, sinology in particular, because of the rise of the People's Republic of China in the 1950s.